Calculation of Mobile Machine Oscillations in view of Internal Processes in Pneumo- hydraulic Suspension - M. I. Zhilevich (Наука и техника)
The paper contains methods, calculated scheme and mathematical model for investigation of oscillations of a mobile machine with a pneumohydraulic suspension. Peculiar feature of the model resides in that it is necessary to take into account nature of internal dynamic processes occurring in damping and elastic elements of the suspension. A pneumohydraulic cylinder is considered as an independent dynamic subsystem integrated in multimass mechanical oscillatory model of an automobile. It enables to analyze the rate of influence of design parameters of suspension cylinders and properties of a working body on output parameters of automobile oscillations and also to select rational values of these parameters. The examples of calculation of a two-mass oscillatory system with a pneumohydraulic suspension cylinder are given in the paper.